Adherence to international dietary recommendations in association with all-cause mortality and fatal and non-fatal cardiovascular disease risk: a prospective analysis of UK Biobank participants. - Kebbe, M; Gao, M; Perez-Cornago, A; Jebb, SA; Piernas, C (BioMed Central, 2021)
Background International dietary guidelines aim to reduce risks of all-cause mortality, cardiovascular disease (CVD), and fatal CVD often associated with poor dietary habits. However, most studies have examined associations with individual nutrients, foods, or dietary patterns, as opposed to quantifying the pooled health effects of adherence to international dietary recommendations. We investigated associations between total adherence to the World Health Organization (WHO) dietary recommendations for saturated fats, free sugars, fibre, and fruits and vegetables and all-cause mortality and fatal and non-fatal CVD. Methods We included participants from the UK Biobank cohort recruited in 2006-2010, which provided at least two valid 24-h dietary assessments. We defined adherence to dietary recommendations as ≤ 10% saturated fats, ≤ 10% free sugars, ≥ 25 g/day fibre, and ≥ 5 servings of fruits and vegetables/day. Multivariable Cox-proportional hazards models were used to investigate prospective associations with all-cause mortality and fatal and non-fatal CVD. In cross-sectional analyses, multivariable linear regression was used to examine associations with cardiometabolic risk factors. Results Among 115,051 participants (39-72 years), only 29.7%, 38.5%, 22.3%, and 9.5% met 0, 1, 2, or 3-4 recommendations, respectively. There was a lower risk of all-cause mortality among participants meeting more dietary recommendations (Ptrend < 0.001), with a significantly lower risk among participants meeting 2: HR 0.91 (95% confidence interval [CI] 0.85-0.97) and 3-4: HR 0.79 (95% CI 0.71-0.88) recommendations. There was no trend with CVD risk, but a significantly lower risk of fatal CVD with 3-4 recommendations: HR 0.78 (95% CI 0.61-0.98). Meeting more recommendations resulted in significant cross-sectional trends (Ptrend < 0.001) towards lower body fat, waist circumference, LDL cholesterol, apolipoprotein B, triglycerides, alkaline phosphatase, gamma glutammyltransferase, and hs-CRP, but higher glucose and aspartate aminotransferase. Conclusions Meeting dietary recommendations is associated with additive reductions in premature mortality. Motivating and supporting people to adhere to dietary guidelines may help extend years of healthy life expectancy.